Desenvolvimentismo, Projeto Juína e os Enawene Nawe : violência e representações da branquitude - Corrêa, Noemi dos Reis (2021)
In this research we seek to understand the conflicts established from the developmental project undertaken by the military regime and its consequences for the Enawene Nawe ethnic group in its relationship with non-indigenous people who arrived in the region in the 1970s. Our main hypothesis was that this developmental project it was based on physical and symbolic violence by the state over indigenous groups, this violence is still reproduced today from the representations that non-indigenous people have built about indigenous people and their relationship with “development”. We started from the understanding of an expansion and development policy based on the exploitation and depreciation of human life to the detriment of capital, we concentrated our analyzes on how the relations of state and society took place in the historical context dated from 1970. Gramsci's concepts , Bourdieu, Martins, Foucaut, Mbemb, Agambem, among others, serve as a basis for understanding how a notion of an expanded state, symbolic power, control and domination, biopower, hegemony, violence and necropolitics was constituted. Making it possible to understand the institutionalized prejudice against the indigenous people that, unfortunately, we carry as a legacy of this colonizing process, making these peoples inferior and subjecting them to a process of dehumanization, expropriation of rights and the naturalization of the violence they suffered. The symbolic violence to which the Indians are subjected comes dressed as “truths” built over the years in a Europeanized and ethnocentric perspective and is used to justify the other types of violence to which this population is exposed.